Caenorhabditis elegans susceptibility to gut Enterococcus faecalis infection is associated with fat metabolism and epithelial junction integrity. Issue 1 (December 2016) - Sim, Shuzhen; Hibberd, Martin
Abstract Background Gut bacteria-host interactions have been implicated in the pathogenesis of numerous human diseases, but few mechanisms have been described. The genetically tractable nematode wormCaenorhabditis elegans can be infected with pathogenic bacteria, such as the human gut commensalEnterococcus faecalis, via feeding, making it a good model for studying these interactions. Results An RNAi screen of 17 worm candidate genes revealed that knockdown of the transcription factornhr-49, a master regulator of fat metabolism, shortens worm lifespan upon infection withE. faecalis (and other potentially pathogenic bacteria) compared toEscherichia coli . The functional similarity ofnhr-49 to the mammalian peroxisome proliferator-activated receptors (PPARs) suggests that this is mediated through a link between fatty acid metabolism and innate immunity. In addition, knockdown of eitherdlg-1 orajm-1, which encode physically interacting proteins in theC. elegans epithelial junction, also reduces worm lifespan uponE. faecalis challenge, demonstrating the importance of the intestinal epithelium as an immune barrier. Conclusions The protective roles identified fornhr-49, dlg-1, andajm-1 suggest mechanistic interactions between the gut microbiota, host fatty acid metabolism, innate immunity, and epithelial junction integrity that are remarkably similar to those implicated in human metabolic and inflammatory diseases.